2012
DOI: 10.1371/journal.pone.0051403
|View full text |Cite
|
Sign up to set email alerts
|

The Crz1/Sp1 Transcription Factor of Cryptococcus neoformans Is Activated by Calcineurin and Regulates Cell Wall Integrity

Abstract: Cryptococcus neoformans survives host temperature and regulates cell wall integrity via a calcium-dependent phosphatase, calcineurin. However, downstream effectors of C. neoformans calcineurin are largely unknown. In S. cerevisiae and other fungal species, a calcineurin-dependent transcription factor Crz1, translocates to nuclei upon activation and triggers expression of target genes. We now show that the C. neoformans Crz1 ortholog (Crz1/Sp1), previously identified as a protein kinase C target during starvati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
98
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(110 citation statements)
references
References 39 publications
10
98
0
Order By: Relevance
“…These observations are consistent with the finding in S. cerevisiae that the cyclin-dependent kinase complex Pho80-Pho85 and PKA negatively regulate the transcription factor Crz1, the major target of calcineurin (90,91). The Crz1 ortholog in C. neoformans influences growth at high temperature, the response to oxygen limitation, cell wall biosynthesis, fluconazole sensitivity, and biofilm formation in a calcium-dependent manner (92,93). In this context, it is interesting that recent work with Candida glabrata revealed that the aspartyl protease CgYps1 (yapsin 1) influences vacuolar and ion homeostasis, cell wall remodelling, calcineurin sensitivity, and polyphosphate levels (94).…”
Section: Discussionsupporting
confidence: 91%
“…These observations are consistent with the finding in S. cerevisiae that the cyclin-dependent kinase complex Pho80-Pho85 and PKA negatively regulate the transcription factor Crz1, the major target of calcineurin (90,91). The Crz1 ortholog in C. neoformans influences growth at high temperature, the response to oxygen limitation, cell wall biosynthesis, fluconazole sensitivity, and biofilm formation in a calcium-dependent manner (92,93). In this context, it is interesting that recent work with Candida glabrata revealed that the aspartyl protease CgYps1 (yapsin 1) influences vacuolar and ion homeostasis, cell wall remodelling, calcineurin sensitivity, and polyphosphate levels (94).…”
Section: Discussionsupporting
confidence: 91%
“…Our previous findings established that, similar to other fungal species, C. neoformans calcineurin is activated by the addition of exogenous calcium to the growth medium (12). Furthermore, in filamentous fungi, addition of calcium restored some of the defects observed in the ⌬plc1 mutant, such as growth rate in Cryphonectria parasitica, and formation of infection structures (appressoria) in Magnaporthe oryzae (26,27).…”
Section: Figsupporting
confidence: 67%
“…After 4 h of incubation, the cells were treated with calcofluor white (CFW) (2.2 mg/ml) with or without FK506 (10 g/ml) for 1 h. The cells were collected and snap-frozen. RNA extraction and cDNA synthesis were performed as described previously (12). Real-time PCR was performed using the actin-encoding gene (ACT1) for normalization.…”
Section: Gene Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, one of the well characterized substrates of calcineurin is the mammalian NFAT ortholog, Crz1, which mediates transcriptional response triggered by calcineurin activation in response to stress conditions in Candida species, C. neoformans 64,[95][96][97] and A. fumigatus. 98,99 As mentioned earlier, another important binding partner of calcineurin is the calcineurin binding protein, Cbp1, an element involved in fine tuning of calcineurin signaling that was also characterized from C. neoformans and A. fumigatus.…”
Section: Primary Targets Of the Calcineurin Signaling Pathwaymentioning
confidence: 99%